PENERAPAN TEAM GAMES TOURNAMENT UNTUK MENINGKATKAN HASIL BELAJAR PENDIDIKAN KEWARGANEGARAAN SDN 09 SUJAH BENGKAYANG - Marsiati, Marsiati; Marzuki, Marzuki; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe purpose of this study is to describe the improvement of student learning outcomes on the learning of Citizenship Education by using cooperative learning model of Team Games Tournamnet (TGT) in the fourth grade of elementary school 09 Sujah Bengkayang Regency. The research method used in this research is descriptive, the form of research that is classroom action research, the nature of research is collaborative. Subjects in this study are students of class IV which amounted to 32 students. The research procedure includes four stages: Planning, Implementation, Observation and Reflection. This study was conducted three cycles, the results obtained are the ability of teachers in planning the learning cycle I is 3.70, cycle II 3.80, cycle III 3.90. The ability of teachers in implementing learning in the first cycle is 3.50, cycle II 3.73, cycle III 3.91 There is an increase in learning outcomes in the first cycle average of 82.00 to 86.19 and 92.24 in the second cycle and third. There is an increase in the learning outcomes of Citizenship Education on the application of cooperative model of Team Games Tournamnet type in grade IV elementary school 09 Sujah, Bengkayang. Keywords: Team Games Tournament, Learning Outcomes, Citizenship Education.